2014
DOI: 10.4102/sajce.v4i1.46
|View full text |Cite
|
Sign up to set email alerts
|

An error analysis in the early grades mathematics – a learning opportunity?

Abstract: <p>Error analysis is the study of errors in learners’ work with a view to looking for possible explanations for these errors. It is a multifaceted activity involving analysis of correct, partially correct and incorrect processes and thinking about possible remediating strategies. This paper reports on such an analysis of learner tests. The tests were administered as part of the evaluation of an intervention project that aimed to teach mathematical problem solving skills to grade 1-4 learners. Quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 19 publications
0
51
0
9
Order By: Relevance
“…According to Herholdt and Sapire [30], partially correct answers indicated that the pupils were aware of the correct operation that needed to be done, but did not complete the operation correctly. This indicates some conceptual understanding, even though there were procedural errors made in the solutions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Herholdt and Sapire [30], partially correct answers indicated that the pupils were aware of the correct operation that needed to be done, but did not complete the operation correctly. This indicates some conceptual understanding, even though there were procedural errors made in the solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of errors establishes an important source for teachers [29]. Errors disclose the type of understanding used by the student when establishing the answer to the question given [30]. Thus, analysis of errors is suitable as a critical indication for teachers in understanding the knowledge used by the students in an activity.…”
Section: Error Analysis In Mathematicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prevention of errors such as the above needs to be done because it will be fatal to other material errors. The causes of elementary school students' mistakes in solving problems are mostly due to the lack of conceptual understanding (Herholdt & Sapire, 2014). Besides, mistakes arise as a result of student learning difficulties.…”
Section: Introductionmentioning
confidence: 99%